Expression of nucleotide-binding oligomerization domain-like receptor protein 1 in patients with acute myocardial infarction and its relationship with clinical prognosis - Qian, Wenhao; Liu, Chang; Chen, Zheng; Wu, Di; Wang, Jianhua; Yao, Han; Li, Fangfang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute myocardial infarction (AMI) remains the leading cause of cardiovascular-related mortality worldwide, with inflammation significantly influencing its progression and prognosis. Nucleotide-binding oligomerization domain-like receptor protein 1 (NLRP1), a key inflammasome regulator, facilitates the release of pro-inflammatory factors. However, its expression profile in AMI and its relationship with inflammation and prognosis are not well understood.MethodsA total of 245 AMI patients (undergoing emergency percutaneous coronary intervention within 12 h), 60 patients with unstable angina (UA), and 60 healthy controls were included. Serum NLRP1 levels were detected by enzyme-linked immunosorbent assay, and clinical indicators were measured. The AMI patients were followed up for 6 months to record major adverse cardiovascular events (MACE). Correlation analysis, regression models, and receiver operating characteristic (ROC) curves were used to evaluate its prognostic value.ResultsSerum NLRP1 levels increased with the severity of the disease (healthy controls < UA < AMI, P < 0.05) and were significantly correlated with inflammatory markers [such as high-sensitivity C-reactive protein and systemic inflammatory response index (SIRI)] and myocardial injury markers [such as high-sensitivity cardiac troponin T (hs-cTnT)] in AMI patients (P < 0.05). A 6-month follow-up showed that AMI patients with MACE had higher NLRP1 levels (P < 0.001), and NLRP1 was an independent risk factor for MACE (odds ratio = 1.01, P = 0.013). Stratified analyses showed that NLRP1 added predictive value, particularly in patients with low hs-cTnT and low SIRI, improving the area under the curve (AUC) (P < 0.05). The ROC curve indicated that NLRP1 alone had an AUC of 0.718 for predicting MACE, which increased to 0.822 when combined with traditional markers (P < 0.05). Category-free net reclassification improvement (NRI) analysis showed a significant improvement in risk reclassification (NRI = 0.315, P = 0.037).DiscussionSerum NLRP1 levels correlate with coronary heart disease severity, indicating inflammation and myocardial injury, and independently predict short-term MACE in AMI. When combined with traditional markers, NLRP1 enhances prognostic assessment efficiency and holds potential as a novel inflammatory marker.